Analisis Morfologi Doa dalam al-Qur’an Surat al-Baqarah 186 - Istiqomah, Himatul (Institut Agama Islam Negeri (IAIN) Curup, 2019)
This study not only aims to discribe derivation of the word do?a, but also composition of do?a. For this purpose, researcher uses qualitative descriptive method with morphological analysis. The result shows that the word do?a in Surah al-Baqarah 186 is mentioned three times with derivation form: ????; gerund = praying, ?????; subject = prayer, dan ???; past verb = prayed. In addition, there are two things in the composition of doa, namely istijabah (?????????? ??) = hard work and iman (???????? ??) = confidence. So, whoever want to be responded by God, he must do both of those things. Indeed, since someone prayed to God, from that time God also began to respond to his do?a.